Re-viewing fascism : Italian cinema, 1922-1943 - Reich, Jacqueline, 1965-; Garofalo, Piero (Indiana University Press, 2002)
When Benito Mussolini proclaimed that "Cinema is the strongest weapon," he was telling only half the story. In reality, very few feature films during the Fascist period can be labeled as propaganda. Re-viewing Fascism considers the many films that failed as "weapons" in creating cultural consensus and instead came to reflect the complexities and contradictions of Fascist culture. The volume also examines the connection between cinema of the Fascist period and neorealism -- ties that many scholars previous
Keywords: Motion pictures -- Italy -- History.; Fascism and motion pictures -- Italy -- History.; Cinéma -- Italie -- Histoire.; Fascisme et cinéma -- Italie -- Histoire.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- General.; Fascism and motion pictures; Motion pictures; Italy; Filmkunst.; Fascisme.; Italië; History